Characterization of heart failure patients with reverse left ventricular remodelling post‐angiotensin receptor blockers/neprilysin inhibitors therapy - Leonid Maizels; Yishay Wasserstrum; Boris Fishman; Amitai Segev; David Ben‐Nun; Anan Younis; Dov Freimark; Israel Mazin; Avishay Grupper (ESC Heart Failure)
Abstract Aims To assess the effect of angiotensin receptor blockers/neprilysin inhibitors (ARNI) on left ventricular (LV) ejection fraction (LVEF) and LV dimensions in a real‐life cohort of heart failure and reduced ejection fraction (HFrEF) patients, while analysing patient characteristics that may predict reverse LV remodelling. Methods and results The ARNI‐treated HFrEF patients followed at a single tertiary medical centre HF‐outpatient clinic were included in the study. Clinical and echocardiographic parameters were evaluated prior to ARNI initiation, and while on ARNI therapy, assessing patient characteristics associated with reverse LV remodelling. The cohort included 91 patients (mean age 60.5 years, 90% male) and 47 (52%) patients exhibited ARNI responsiveness, defined as an increase in LVEF during therapy. Overall, LVEF increased by 19% post‐ARNI (23.8 to 28.4%, P < 0.001). Subgroup analysis revealed several parameters associated with significant LVEF improvement, including baseline LVEF <30%, non‐ischaemic HF aetiology, lack of cardiac resynchronization therapy (CRT), better initial functional class and ARNI initiation within 3 years from HF diagnosis (P ≤ 0.001 for all). Significant reduction in LV dimensions was noted in patients with lower initial LVEF, non‐ischaemic HF and no CRT. Further combined subgrouping of the study population demonstrated that patients with both LVEF <30% and a non‐ischaemic HF gained most benefit from ARNI with an average of 51% improvement in LVEF (19.9 to 30%, P < 0.001). Conclusions The ARNI treatment response is not uniform among HFrEF patient subgroups. More pronounce reverse LV remodelling is associated with early ARNI treatment initiation in the course of HFrEF, and in those with LVEF <30%, non‐ischaemic HF and no CRT.